Long term mortality in a population-based cohort of adolescents, and young and middle-aged adults with burn injury in Western Australia: A 33-year study - Duke, J.; Boyd, James; Randall, S.; Wood, F. (2015)
© 2015 Elsevier Ltd. All rights reserved. Background Advances in the treatment and management of burn patients over the past decades have resulted in a decline of in-hospital mortality rates. Current estimates of burn-related mortality are usually in the context of deaths occurring during the admission or within a short time period after the incident burn. Limited data are available that examine long term mortality after burn injury. This study aimed to assess the impact of burn injury on long-term mortality and quantify any increased risk of death attributable to burn injury. Methods A population-based cohort study of persons 15-44 years of age hospitalised for burn injury (n = 14,559) in Western Australia (1980-2012) and a matched non-injured comparison group (n = 56,822) using linked health administrative data was used. Hospital morbidity and death data were obtained from the Western Australian Hospital Morbidity Data System and Death Register. De-identified extraction of all linked hospital morbidity and death records for the period 1980-2012 were provided by the Western Australian Data Linkage System. Survival analysis was conducted using the Kaplan-Meier method and Cox proportional hazards modelling. Results The adjusted all-cause Mortality Rate Ratio (MRR) for burn injury was 1.8 (95%CI: 1.7-2.0); those with burn injury had a 1.8 times greater rate of mortality than those with no injury. The index burn injury was estimated to account for 44% of all recorded deaths in the burn injury cohort during the study period after discharge. Increased risk of mortality was observed for both severe (MRR, 95%CI: 1.9, 1.3-2.9) and minor (MRR, 95%CI: 2.5, 2.2-3.0) burns. Conclusions An increased risk of long-term all-cause mortality is associated with both minor and severe burn injury. Estimates of total mortality burden based on the early in-patient period alone, significantly underestimates the true burden of burn injury in adolescents, and young and middle aged adults. These results have significant implications for burn injury prevention.